Integration of Educational Games in Increasing Motivation and Results Student Learning in the Subject of Islamic Cultural History at MTS N 1 Wonosobo - Alfi Rohmatina Zulva; Robingun Suyud El Syam; Abdul Majid; Salis Irvan Fuadi; Ngarifin Shidiq; Siti Lailatul Ulya (World Journal of Islamic Learning and Teaching, 2026)
This study aims to: (1) describe the integration of educational games in Islamic Education (SKI) learning; (2) understand students' learning experiences in learning Islamic cultural history in classes that integrate educational games; (3) examine the impact on the learning outcomes of class VIII students of MTs N 1 Wonosobo Research. This study uses a qualitative approach with a phenomenological research type. The research subjects include SKI subject teachers, madrasa principals, and class VIII students of MTs N 1 Wonosobo Research. Data collection techniques were carried out through in-depth interviews, observation of the learning process, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that the integration of educational games in Islamic Education (SKI) learning is implemented in a planned and contextual manner as part of the teacher's learning strategy. The use of educational games can increase student learning motivation which is characterized by increased enthusiasm, activeness, focus, and student participation in the learning process. In terms of learning outcomes, the percentage of student learning completion before and after the educational game integration both reached 100%, with a Minimum Completion Criteria (KKM) of 68. However, the average (mean) student learning outcomes increased from 94.28 to 95.17, an increase of ±0.95%. This finding indicates that the integration of educational games not only maintains learning completion but also improves the quality of students' understanding of the Islamic Cultural History material. Thus, the integration of educational games has proven to be an effective learning innovation in improving student motivation and learning outcomes in the subject of Islamic Cultural History.